Genome-wide identification of the B3 transcription factor family in pepper (Capsicum annuum) and expression patterns during fruit ripening - Tao Wang; Cha Long; Meixia Chang; Yuan Wu; Shixian Su; Jingjiang Wei; Suyan Jiang; Xiujun Wang; Jianwen He; Dan Xing; Yangbo He; Yaoqi Ran; et al. (Scientific Reports, 2024)
Abstract In plants, B3 transcription factors play important roles in a variety of aspects of their growth and development. While the B3 transcription factor has been extensively identified and studied in numerous species, there is limited knowledge regarding its B3 superfamily in pepper. Through the utilization of genome-wide sequence analysis, we identified a total of 106 B3 genes from pepper (Capsicum annuum), they are categorized into four subfamilies: RAV, ARF, LAV, and REM. Chromosome distribution, genetic structure, motif, and cis-acting element of the pepper B3 protein were analyzed. Conserved gene structure and motifs outside the B3 domain provided strong evidence for phylogenetic relationships, allowing potential functions to be deduced by comparison with homologous genes from Arabidopsis. According to the high-throughput transcriptome sequencing analysis, expression patterns differ during different phases of fruit development in the majority of the 106 B3 pepper genes. By using qRT-PCR analysis, similar expression patterns in fruits from various time periods were discovered. In addition, further analysis of the CaRAV4 gene showed that its expression level decreased with fruit ripening and located in the nucleus. B3 transcription factors have been genome-wide characterized in a variety of crops, but the present study is the first genome-wide analysis of the B3 superfamily in pepper. More importantly, although B3 transcription factors play key regulatory roles in fruit development, it is uncertain whether B3 transcription factors are involved in the regulation of the fruit development and ripening process in pepper and their specific regulatory mechanisms because the molecular mechanisms of the process have not been fully explained. The results of the study provide a foundation and new insights into the potential regulatory functions and molecular mechanisms of B3 genes in the development and ripening process of pepper fruits, and provide a solid theoretical foundation for the enhancement of the quality of peppers and their selection and breeding of high-yield varieties.